Wnt signaling in development and disease : molecular mechanisms and biological functions - Hoppler, Stefan, 1965-; Moon, Randall T. (Hoboken, New Jersey : Wiley Blackwell, 2014)
"Widely recognized as one of the most important signaling mechanisms in development and disease, Wnt signaling pathways are networks of proteins that play significant roles in embryogenesis or cancer development. Wnt Signaling in Development and Disease addresses the fundamentals of Wnt signaling and delves into molecular pathway mechanisms, its role in embryogenesis, adult tissue homeostasis, and chronic disease. This comprehensive resource details current knowledge of Wnt signaling while looking ahead to future progress"--Provided by publisher.
Machine generated contents note: Part A: Molecular Signaling Mechanisms: from Pathways to Networks -- Chapter 1: Sending of the Wnt signal and its reception at the membrane (an overview) / Xi He, Rik Korswagen -- Chapter 2: Introduction to Wnt Signal transduction in the cytoplasm / Xi He -- Chapter 3: Regulation of gene expression by Wnt signaling in the nucleus (an overview) / Marian Waterman, Ken Cadigan -- Chapter 4: Wnt target genes: Insights from bioinformatics / Ken Cadigan -- Chapter 5: Introduction to [beta]-catenin-independent Wnt signaling pathways / Michael Kuhl, David Strutt -- Chapter 6: Choice and specificity of Wnt signaling pathways / Guido Zaman, Stuart Aaronson -- Chapter 7: The Cell Biology of Wnt signaling / John Wallingford, Kikuchi -- Chapter 8: New insights from proteomic analysis of Wnt signaling / Ben Major -- Chapter 9: New insights about Wnt pathway mechanisms from global siRNA screens / Ram Dasgupta -- Chapter 10: Insights from mathematical modeling on Wnt signaling network / M. Kuhl -- Chapter 11: The evolution of Wnt signaling / Jenifer Croce (David McClay), Thomas Holstein, Linda Holland -- Part B: Selected key molecules in Wnt signaling -- Chapter 12: The Wnt signal / Roel Nusse, Karl Willert -- Chapter 13: Secreted Wnt inhibitors or modulators / Herbert Steinbeisser, Robert Kypta, Masanori Taira, Paola Bovolenta and Javier Lopez-Rios -- Chapter 14: Frizzleds as G-Protein Coupled Receptors / Gunnar Schulte (Craig Malbon and Randall Moon) -- Chapter 15: Dishevelled, at the crossroads of pathways / Mariann Bienz, John Wallinford, Vitezslav Bryja -- Chapter 16: [beta]-catenin, jobs for one protein in signaling and cell adhesion / Jonathan Pettitt, Cara Gottardi, Koni Basler, Bienz -- Chapter 17: Variety of TCF/LEF structure and function in vertebrate Wnt signaling / Mariann Waterman, Hoppler, Bradley Merrill -- Chapter 18: Insights from Structural Analysis of protein-protein interactions by Wnt Pathway Components and functional multi-protein complex formation / Wenqing Xu -- Part C: Wnt Signaling in Embryonic Development and Adult Tissue Homeostasis -- Chapter 19: Wnt signaling in Early embryonic development: From Fertilization To Gastrulation (an introduction) / Stefan Hoppler -- Chapter 20: Wnt signaling in Embryonic Stem Cells: Insights into Early Mammalian Development / Kathy Davidson -- Chapter 21: Wnt signaling specifying Neural Lineages / Corinne Houart, Richard Dorsky -- Chapter 22: Wnt signaling in Heart Organogenesis / Morressey, Hoppler, M. Kuhl -- Chapter 23: Wnt signaling in Kidney organogenesis / Andy McMahon, Seppo Vainio -- Chapter 24: Wnt signaling regulation of tissue architecture (EMT and MET) and morphogenesis / Liz Vincan -- Chapter 25: Wnt Signaling in Tissue Homeostasis in Adults / Elaine Fuchs, Hans Clevers -- Chapter 26: Restoring Tissue Homeostasis: Wnt Signaling in Tissue Regeneration After Acute Injury / Author tbd -- PART D: Wnt Signaling In Chronic Disease -- Chapter 27: Wnt signaling in Disease (an overview) / Randall Moon -- Chapter 28: Wnt signaling in Colorectal Cancer / Paul Polakis or Riccardo Fodde, Owen Sansom -- Chapter 29: Wnt signaling in Melanoma / Andy Chien -- Chapter 30: Wnt signaling in psychiatric disease and dementia / Stephen Haggarty -- Chapter 31: Wnt signaling Therapeutics / Trevor Dale, Randall Moon, et al.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Wnt Proteins -- physiology; Wnt proteins; Cellular signal transduction; SCIENCE -- Life Sciences -- Biochemistry; Cellular signal transduction; Wnt proteins; Electronic books; Electronic books